Paciente de sexo masculino con 40 años de edad que presenta síndrome metabólico - Burgos Mosquera, Kerly Silvana (2019)
The following clinical case study is based on a 40-year-old male patient, who suffers from metabolic syndrome, has a family pathological history, Diabetes Mellitus. As a result of the physical examination I have high blood pressure, the anthropometric assessment reveals the body mass index of 33.2 kg / tm2. According to the cut-off points of the World Health Organization, presentation of a nutritional status of obesity grade I. The comprehensive nutritional diagnosis will be carried. out by means of the anthropometric parameters, the obvious biochemical values, a high lipid profile; a high fasting blood sugar; and as regards dietary evaluation or food history, an excessive intake of macronutrients is evident. Our goal is to improve the nutritional status of the patient through a correct nutritional intervention, with a 1,500 kcal / day, low fat, and high fiber diet plan, controlling sodium and potassium. Fractioned into 5 meals a day according to your caloric requirements, in order to reduce cardiovascular risks, and thus provide improvement in the patient's quality of life and eating habits avoiding complications in the future.